(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The article is devoted to the analysis of the structure of the Soviet political anecdote of a special type considered in the context of the postmodernism poetics. This type of anecdote is based on the playful deconstruction of the late Soviet official ideological discourse, the distinctive features of which were: high saturation of quotations, presupposition of the truth of an utterance created by transformations of the syntactic structures nominalization, fundamental absence of the author’s position, and isolation of logical and narrative structures. In the functioning of the Soviet official ideological discourse we can clearly trace the tendencies towards an increase in the role of pragmatic factors and a decrease in the semantic component. These features of discourse are transformed into a playable form in a postmodern political anecdote. The anecdote can be based on a ‘proof’ of the quoted position of the ideological official discourse, which removes the quotation from the zone of ritual communication and offsets its performative function. Different types of discourses can be juxtaposed in an anecdote, which leads to semantic, referential, and illocutionary ambiguity. This article analyzes specific linguistic means and methods of breaking the logical and narrative isolation of the initial discourse and creating a comic effect in an anecdote.